Low-Fidelity, In Situ, Accessible Pediatric Mass Casualty Incident Simulation to Evaluate and Improve Pediatric Readiness - Sydney E. Jeffs; Cathlyn K. Medina; Parker Frankiewicz; Steven W. Thornton; Elizabeth Horne; Smith Ngeve; Tara Thomason; Delaney Anani-Wolf; Catherine B. Beckhorn; Delaney James; Rachel Hobbs; Remi Hueckel; et al. (MedEdPORTAL, 2025)
Introduction Existing mass casualty incident (MCI) simulations rely on high-fidelity patient simulators, which are cost-prohibitive and often exclude pediatric patients. To address the need for deployable, low-fidelity pediatric MCI simulations, we developed and evaluated a cost-conscious model to teach the principles of JumpSTART, the pediatric variation of the Simple Triage and Rapid Treatment (START) algorithm. Methods In this low-fidelity pediatric MCI simulation, pediatric trauma patients were represented by 2D, life-sized drawings including all pertinent information for triage using JumpSTART. Learners were prehospital and hospital staff with multidisciplinary backgrounds. Learners were divided into two groups and assigned five unique patients across triage and acuity levels. Primary outcomes were the accuracy of assigned triage categories and Broselow lengths, and time to triage completion. Postsimulation surveys were designed to assess learner attitudes about the exercise. Results Two sessions of the pediatric MCI simulation were conducted (18 and 16 participants, respectively). Triage categories were correctly assigned using JumpSTART for 9 of 10 patients in cohort 1. One patient was over-triaged. All patients in cohort 2 were correctly assigned triage categories. Broselow lengths were correctly assigned to all patients. Median time to assign a triage category per patient was 67 seconds (range 30–135) for the first cohort and 64 seconds (range 30–116) for the second. Participant feedback was universally positive. Discussion We present an accessible, low-fidelity training model for pediatric MCI, which creates a simple but dynamic hands-on experience for participants around the JumpSTART pediatric triage algorithm and is replicable across environments.